Nursing care for patients with endometriosis and/or adenomyosis: A mixed methods systematic review protocol. Issue 4 (August 2021) - O'Donoghue, Erica; Kapp, Suzanne; Murphy, Tracy; Kusljic, Snezana
ABSTRACT: Background: Endometriosis and adenomyosis are benign gynaecological conditions that can cause pain disorders, menstrual abnormalities, and fertility issues. Due to the variances of clinical presentations, a patient-centred care approach is needed to address the complex healthcare needs of individuals with endometriosis and/or adenomyosis. This approach can be achieved by nurses both independently, such as in nurse-led clinics, and in collaboration with other healthcare professionals. Aim: The review aims to examine the nurse's role in the delivery of care for patients with endometriosis and/or adenomyosis. An overall research question focuses on: 'How do nurses deliver care for patients with endometriosis and/or adenomyosis?' Methods: A mixed methods systematic review will be undertaken using a convergent segregated design approach guided by the relevant Joanna Briggs Institute (JBI) methodology. A three-step search strategy will be applied across six databases to locate qualitative, quantitative, and mixed method studies which meet the inclusion criteria. At least two independent reviewers will be involved in screening, critical appraisal, and data extraction of included studies. Results will be tabulated and accompanied by a narrative summary. Conclusion: Examination of the review topic and answering the research question will result in a synthesis of evidence of the nurse's role in the delivery of care for patients with endometriosis and/or adenomyosis. Recommendations may inform in the planning and development of the nurses' role which has the potential to improve the quality of healthcare for patients with endometriosis and/or adenomyosis.